ISLAMIC SOCIAL ENTREPRENEURSHIP MODEL IN ISLAMIC BOARDING SCHOOL (STUDY ON PABS) - Hafidloh,; Hasany, Ahmad; Toyiburahman,; Ma'mun,; Maryani, (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Islamic Social Entrepreneurship from the Islamic boarding school perspective has not been studied much, as has the implications of change management theory with the ADKAR concept. This study aimed to determine Islamic social entrepreneurship model in Islamic Boarding School. Reseach methods employed an ethnographic research case study with an inductive qualitative approach. The data was processed using NVIVO 12. This study contributes to a deeper understanding of Islamic Social Entrepreneurship (ISE) from the Islamic boarding school perspective. By adopting Good Corporate Governance, this study shows how changes in management structure, use of information technology, and human resource development through the implicit application of the ADKAR concept can be implemented in the context of Islamic boarding schools to achieve economic independence and sustainability. This study enriches academic studies in the field of social entrepreneurship by introducing a different model from the perspective of Islamic boarding schools that is in line with Islamic values. From the managerial aspects, this study provides practical guidance for Islamic boarding school managers in developing business units.